Effect of Sustainable Chicken Waste Manure Fertilizer on the Growth of Vigna aconitifolia - Vaishnavi. Ghadage; B.M Gore (Contemporary Research and Perspectives in Biological Science Vol. 6, 2024)
Manure from chicken excrement seems to be a novel and workable method for decomposing trash, which lessens the burden on solid waste management. It appears that chicken manure is a cutting-edge, environment-friendly waste treatment technique that has enormous potential for the future of solid waste management. Due to the high levels of nitrogen, phosphate, and potassium in chicken waste, its use as fertilizer has exceeded that of other waste products from animals, such as pig manure. For 90-100 days, the intestinal material from Gallus gallus domesticus which is degraded and turned into chicken waste manure/ fertilizer. The pH value observed in chicken waste manure is 7.3 respectively. Apart from being a major source of nutrients for crop growth, chicken manure also harbours a number of human diseases. The Vigna aconitifolia is consumed as food and fodder and is known for having a high protein content along with an excellent amino acid, mineral, and vitamin profile. The purpose of the study was to determine how chicken waste manure affected Vigna aconitifolia roots, nodes, leaves, plant height, pods, and seeds. The organic waste decomposer was obtained from the National Centre for Organic Farming in Ghaziabad, Uttar Pradesh, which is rich in macro- and micronutrients that can be used to benefit soil and plants. After 150 days of the study, it was shown that all treated groups that were exposed to a high dose of chicken waste manure showed a significant increase in the number of nodes, leaves, roots, shoot length, leaf length, number of pods, length of pod, and number of seeds. The study found a direct correlation between the growth rate of Vigna aconitifolia seeds and the varied concentrations of chicken waste manure given to the seeds. Chicken waste manure is treated biologically with the help of microbes to improve the micronutrients in the waste which can be used as chicken waste manure/ fertilizer for sustainable agricultural purposes.